The Impact of Vlog-Mediated Speaking on University Students’ Speaking Skill - Mohammad Ikbal; Misdi Misdi; Apandi Apandi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Speaking ability is a crucial component of English language learning as it allows students to express ideas and exchange information effectively. However, many EFL learners continue to face speaking difficulties due to limited vocabulary, pronunciation challenges, low confidence, and insufficient opportunities for oral practice. This study investigates the impact of vlog-mediated speaking activities on university students’ speaking skills and explores their learning experiences during vlog project implementation. A mixed-method approach with a quantitative-dominant design was employed involving 16 students from the English Education Study Program at Universitas Swadaya Gunung Jati (UGJ). Quantitative data were collected from students’ speaking performances across four vlog activities through pre-test and post-test assessments, while qualitative data were obtained from students’ reflective responses. The quantitative data were analyzed using descriptive statistics and paired-sample t-tests, while qualitative data were examined through thematic analysis. The findings showed a consistent improvement in students’ speaking performance, with mean scores increasing from 55.47 in Vlog 1 to 70.31 in Vlog 4. The paired-sample t-test revealed a significant difference between pre-test and post-test scores (t(15) = 5.69, p < .001), with a large effect size (Cohen’s d = 1.42). Qualitative analysis identified three themes: enhanced confidence, improved speaking skills, and positive learning experiences. These results suggest that vlog-mediated speaking activities effectively promote repeated practice, self-reflection, and active engagement in English speaking development.